Effects of a roughened femoral head and the locus of grafting on the wear resistance of the phospholipid polymer-grafted acetabular liner. (1st March 2019) - Moro, Toru; Ishihara, Kazuhiko; Takatori, Yoshio; Tanaka, Sakae; Kyomoto, Masayuki; Hashimoto, Masami; Ishikura, Hisatoshi; Hidaka, Ryo; Tanaka, Takeyuki; Kawaguchi, Hiroshi; Nakamura, Kozo
Graphical abstract: Abstract: Although laboratory tests and mid-term clinical outcomes show the clinical safety and remarkable wear resistance of the highly cross-linked polyethylene (HXLPE) acetabular liner with a nanometer-scaled graft layer of poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), the wear resistance of the layer under severe abrasive conditions is concerning. We evaluated the effects of a roughened femoral head and the grafting locus on the wear resistance of the PMPC-grafted HXLPE liner and the effect of PMPC grafting on wear resistance of the HXLPE substrate by removing the PMPC-grafted layer using a severely roughened femoral head. Against a moderately roughened femoral head, the PMPC-grafted HXLPE liner showed negative wear, although an untreated HXLPE liner increased the wear by 154.1% compared with wear against a polished femoral head, confirming that PMPC grafts were unaffected. Against a severely roughened femoral head, the PMPC-grafted layer of the head contact area might be removed under severe conditions. However, the wear rate was reduced by 52.5% compared to that of untreated HXLPE liners. Moreover, the head non-contact area-modified PMPC-grafted HXLPE liner against a polished femoral head reduced the wear by 76.8% compared with untreated HXLPE liner; thus, this area may be also important in the development of fluid-film lubrication. Statement of significance: Here we describe effects of a roughened femoral head and the locus of grafting on the wear-resistance of the phospholipid polymer grafted highly cross-linked polyethylene (PMPC-HXLPE) liner. Against a moderately roughened femoral head, the PMPC-HXLPE liner showed negative wear, confirming that PMPC grafts were unaffected. After removing the PMPC layer of the head contact area using a severely roughened femoral head, the wear rate not only exceeded that of untreated HXLPE liners, but was reduced by 52.5%, confirming that PMPC grafting does not affect the wear-resistance of the HXLPE substrate. In addition, the head non-contact area-modified PMPC-HXLPE liner reduced the wear by 76.8%. Thus, this area may also may be important in the development of fluid-film lubrication.